(untitled) (Psicologia USP, 2022)
Despite the well-known benefits for health, low levels of physical activity (PA) remain a public health issue. Research on motives for engaging in different PA shows differences in motives for Sports and Exercises. However, few studies addressed motives using more categories of PA. In this research, we investigated motives for four categories of PA (Individual Sports, Collective Sports, Exercises, and Body/Movement Practices), and possible effects of sex and age among 1,420 physically active individuals. Respondents answered the Motivation for Physical Activity Measure Revised. Intrinsic motives were higher for Sports, while Exercisers were motivated more extrinsically. Body/Movement Practices, although being composed of several activities defined by previous studies as Exercises, showed a motivational pattern closer to Sports. Fitness/Health motivation increased with age, while Appearance motivation decreased. Regarding sex, women reported higher Interest/ Enjoyment than men. Our results can have implications for physical activities promotion, especially considering more categories than Sports/Exercises in the context of different motives.